Circ-FOXM1 knockdown suppresses non-small cell lung cancer development by regulating the miR-149-5p/ATG5 axis. Issue 2 (17th January 2021) - Wei, Haitao; Li, Li; Zhang, Haifeng; Xu, Feng; Chen, Longqi; Che, Guowei; Wang, Yun
ABSTRACT: Circular RNAs (circRNAs) have been reported to be related to the development of human cancers. However, the function of circ-FOXM1 in non-small cell lung cancer (NSCLC) was largely unknown. Here, we revealed the role and functional mechanism of circ-FOXM1 in NSCLC progression. The relative expression of circ-FOXM1, microRNA-149-5p (miR-149-5p), and autophagy-related 5 (ATG5) was determined by quantitative real-time polymerase chain reaction (RT-qPCR). Cell Counting Kit-8 (CCK-8), flow cytometry, and transwell assay were employed to assess cell viability, apoptosis, and migration, respectively. The relative protein expression was detected by western blot. Furthermore, mouse xenograft was carried out to analyze the effect of circ-FOXM1 on tumor growth in vivo . In addition, the interaction between miR-149-5p and circ-FOXM1 or ATG5 was predicted by Starbase3.0 and confirmed by the dual-luciferase reporter assay and RNA pull-down assay. Circ-FOXM1 and ATG5 levels were upregulated, while the miR-149-5p level was downregulated in NSCLC tissues and cells. Circ-FOXM1 knockdown suppressed NSCLC cell viability, migration, and autophagy, and induced cell apoptosis. Interestingly, circ-FOXM1 targeted miR-149-5p to upregulate the ATG5 level. Moreover, circ-FOXM1 exerted function through repressing miR-149-5p expression, and miR-149-5p exerted function via inhibiting ATG5 expression. Our results suggested that circ-FOXM1 knockdown attenuated the development of NSCLC through modulating the miR-149-5p/ATG5 axis, providing a theoretical basis for the therapy of NSCLC.